Portraits of Women in East Java Preacher's Content Sermon - Hasanah, Eva Putriya (Nursyam Center, 2023)
This research is motivated by the high phenomenon on violence against women that inspiring researcher to find more information on the da'wah on women. For research purpose, the researcher chosen videos sermon titled on women and related words on YouTube in 2021 to use on three preachers from East Java, namely: QX, QY, and QZ. This is qualitative research using the Critical Discourse Analysis (CDA) from Norman Fairclough and theory used to discuss the research result is symbolic violence theory from Pierre Bourdieu. This research found that each preacher has different results: QX showed verbal violence consistently on his sermon contents. There are three typologies of gender inequality found: sexism, misogyny, and negative stigma. Meanwhile QY and QZ only found one typology, that is sexism, but both did not show any consistency in all video sermons. The existence of these texts is driven by three things: the background of preacher, the condition of audiences, and patriarchal culture.